Mentalizing Makes Parenting Work: A Review about Parental Reflective Functioning and Clinical Interventions to Improve It - Camoirano, Andrea (Frontiers in Psychology, 2017)
In the last decade several studies have investigated the role of parental reflective functioning (RF), defined as the parental ability to understand his/her child’s mental states, on the child’s development. Herein, a narrative review on parental RF is presented aimed at 1) presenting an overview of the existing empirical studies, 2) pinpointing unrequited questions, and 3) identifying future research directions. Specifically, the current review focused on a) the impact of parental RF on the quality of caregiving and the child’s attachment security, b) the effect of parental RF on the child’s emotion regulation and the child’s RF, c) maternal RF in women with a history of neglect and abuse, d) the efficacy of mentalization-based clinical interventions, and e) the recently developed Parental Reflective Questionnaire. The following terms “maternal reflective functioning”, “paternal reflective functioning”, “parental reflective functioning”, “parental mentalization”, “maternal mentalization”, and “paternal mentalization” were searched in titles, abstracts, and main texts using Medline, Web of Science, and Scopus databases. Next, a search in Mendeley was also conducted. Inclusion criteria comprised original articles if they refer to the Reflective Functioning Scale (Fonagy, Target, Steele, and Steele, 1998) and were published in an English language, peer-reviewed journal before July, 2016. According to exclusion criteria, dissertations, qualitative or theoretical papers, and chapters in books were not taken into account. The review includes 47 studies that, taken together, supported the notion that higher parental RF was associated with adequate caregiving and the child’s attachment security, whereas low maternal RF was found in mothers whose children suffered from anxiety disorders, impairment in emotion regulation, and externalizing behaviors. In addition, higher parental RF was associated with better mentalizing abilities in children. However, unexpected findings have emerged from the most recent randomized controlled trials that tested the efficacy of mentalization-based interventions in high risk samples of mothers, raising questions about the suitability of the verbal measures in capturing the mentalizing processes at the root of the parental capacity to be adequately responsive to the child’s emotional needs.